SIFAT FISIS DANMEKANIS PAPAN PARTIKEL DARI SABUT KULIT BUAH NIPAH (Nyfa fruticans Wurmb) - Rosidah Rosidah; Mochamad Arief Soendjoto; Arfa Agustina Rezekiah (Jurnal Hutan Tropis, 2019)
Coco Palm-nypa fruit leather (Nyfa fruticans Wurmb) were usually dumped away and not utilized. This research aims to get a Palm fruit flour composition variations as extender on urea adhesive formaldehyde; and physical and mechanical properties of the tested particle board that it generates. Particle board raw materials used 100% of the Coco Palm fruit leather. The adhesive used is urea formaldehyde with a Palm fruit flour composition variations as extender is A = 100% flour nypa, B = 75% of Palm starch and wheat flour, 25% C = 50% flour nypa and 50% wheat flour, D = 25% nypa flour 75% wheat flour , and e. 100% wheat flour. To test the influence of the treatment to physical mechanical properties, the Complete Random Design was applied. The results showed that variations of the extender composition Palm fruit flour to urea formaldehyde adhesive has no significance effect to the water content value, but have significant effect to firmness of broken (MoR) and supple dependability (MoE).